The Effect of Access and Facilities of Drop Zone Area on Passenger Satisfaction at Sultan Hasanuddin International Airport Makassar - Riska Wulandari; Septiyani Putri Astutik (CV. Rayyan Dwi Bharata, 2023)
Access and drop zone facilities are very important things that must be considered by every airport, including Sultan Hasanuddin Makassar Airport. From the observations made by researchers, there are still passengers who complain about the distance to the drop zone access area to the terminal and the availability of trolly facilities in the Drop Zone Area which have not been provided by the management of Sultan Hasanuddin Makassar International Airport. This study aims to 1) determine the effect of access on passenger satisfaction at Sultan Hasanuddin International Airport Makassar, 2) determine the effect of Drop Zone Area facilities on passenger satisfaction at Sultan Hasanuddin International Airport Makassar Drop Zone Area services, 3) determine the effect of access and facilities Drop Zone Area on passenger satisfaction at Sultan Hasanuddin International Airport Makassar, 4) determine the influence of access and Drop Zone Area facilities on passenger satisfaction at Sultan Hasanuddin International Airport Makassar. This research uses quantitative methods. This research was carried out in the period 1 June - 1 July 2023 with the object of research in the departure area of Sultan Hasanuddin Makassar International Airport. The research sample was determined by 100 respondents. The research data were analyzed using multiple linear regression analysis with the help of IBM SPSS version 22 software. The results of this study indicate that there is a positive effect of access on passenger satisfaction at Sultan Hasanuddin International Airport. Meanwhile this study shows that there is a positive effect of the drop zone facility on passenger satisfaction at Sultan Hasanuddin International Airport. This research also shows that the provision of airport drop zone facilities is inseparable from passenger expectations, so this is a serious part of fulfilling passenger satisfaction. Meanwhile, together they have a positive and significant effect on passenger satisfaction at Sultan Hasanuddin Makassar International Airport. Then these results show that access and drop zone facilities affect passenger satisfaction at Sultan Hasanuddin Makassar Airport by 83.5%.